A Comparative Study of Quality of Life of Patients Who Underwent Total Laparoscopic Hysterectomy and Total Abdominal Hysterectomy - Shina Oranratanaphan; Natacha Poolcharoen; Chai Aiyasriwatthana; Pongkasem Worasethsin (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: To evaluate the effect of total laparoscopic hysterectomy (TLH) on the quality of life compares to total abdominal hysterectomy (TAH) method in Thailand.Materials and Methods: After approval from ethical committee was achieved, the study was conducted. Euro-quality of life five dimensions (EQ-5D) questionnaire was used to evaluate quality of life. The questionnaire was given to the patients before surgery, day 1, 7 and 28 after operation. The patients were already assigned to perform TAH or TLH by their voluntariness. General characteristics and operative procedure including complications were also recorded. Data analysis was performed by using SPSS version 22. Results: Hundred cases of TAH and 102 cases of TLH were collected. Baseline characteristics, diagnosis, operative time and complication rate were not difference. Educational level and income were slightly higher in TLH group. TLH had less blood loss and shorter hospital stay and had tendency to mobilize better than TAH group. The other aspects of quality of life such as pain, self-care and doing usual activity were similar. Anxiety score in both groups were improved after the operation. Conclusion: TLH can reduce blood loss, hospital stay without increasing the complications. There were slightly differences in quality of life between group and the differences were found in only short term after the operation. TLH still had the benefit on faster recovery, shorter hospital stay and less blood loss.